The impact of the corrective and stability exercises program on the quality of basic movement patterns among dance students - Skotnicka, Marta; Karpowicz, Krzysztof; Bartkowiak, Sylwia; Strzelczyk, Ryszard (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Based on the kinetic chain model, in which the body is a linked system of interdependent and working in a proximal to distal order segments, the main task of the core is to stabilize the kinetic chain during functional movements. Poor core stability and muscle imbalance are factors that may contribute to injuries. By detecting imbalances, deficits and asymmetries in basic movement patterns, there is a tool which can provide the basis for the implementation of preventive strategies. Aim of Study. The main purpose of the present study is to verify the effectiveness of the corrective and stability exercises program on the quality of basic movement patterns among dance students. Material and Methods. The study was perform on 18 female students of first year of the Dance in physical culture from University of Physical Education in Poznan, Poland, who were divided into 2 groups: intervention (n = 9) and control (n = 9). In both groups, were carried out pre- and post-test. The quality of basic movement patterns was evaluated by the Functional Movement Screen, consisted of seven tests: deep squat, hurdle step, in-line lunge, shoulder mobility, active straight leg raise, trunk stability push-up, rotary stability. In the intervention group was introduced the program of corrective exercises based on the obtained results enriched with core stability exercises. After 12-week training program, the quality of basic movement patterns were assessed again in both groups. Results. The research found out that at the pre-test there was no significant differences between both groups. However, the groups differed significantly (p < 0.05) at post-test in terms of the overall result of the FMS and 2 tests: deep squat and in-line lunge. Significant post training changes were noted for the intervention group in the overall FMS scores and 4 tests: deep squat, hurdle step, in-line lunge, trunk stability push-up. Significant changes were also found in the control group in the overall FMS results and in the deep squat test. Conclusions. The identification of the “weakest links” of kinetic chain, integrated with properly planned and conducted corrective exercises, enriched with core stability exercises may positively impact on the quality of basic movement patterns, which seems to be the starting point for determining the possibility of used tool to prevent injuries
Keywords: Functional Movement Screen; FMS; intervention program; training; core stability